Analysis of the famous international scrum-half technique of rugby player and its significance to rugby training education - Zhang, Z. (2020 International Conference on Educational Training and Educational Phenomena (ICETEP2020), Wenzhou, China, from 2020-06-27 to 2020-06-29, 2020)
This study analysis the scrum-half technique of Australia team captain "George Gregan" of the man rugby (fifteens) "World Cup" championship. It reveals that the movement process, technical details and implementation of the scrum-half of the world`s highest-level pass ball player in rugby so that reasonable guidance (references) and specialized training focused on pass could be provided for the current rugby training education.